Dissecting the molecular interplay between tomato spotted wilt virus and the insect vector, Frankliniella occidentalis - Badillo-Vargas, Ismael (Kansas State University, 2014)
The Bunyaviridae is a family of animal and plant viruses that pose a threat to human, animal, and plant health worldwide. In nature, the dissemination of these viruses is dependent on arthropod vectors (genera Orthobunyavirus, Nairovirus, Phlebovirus, and Tospovirus) or rodent vectors (genus Hantavirus). The genus Tospovirus is the only one within this virus family that is composed of plant-infecting viruses transmitted by thrips. Tomato spotted wilt virus (TSWV), the type species of the Tospovirus genus, is one of the ten most devastating plant viruses known. It is most efficiently transmitted by the western flower thrips, Frankliniella occidentalis Pergande, in a persistant propagative manner. The insect molecules associated with virus infection and transmission by the thrips vector remain unidentified to date. The aim of this work was to identify F. occidentalis larval thrips proteins that are differentially expressed during TSWV infection of the insect vector and those that directly interact with TSWV. To achieve these goals, I used two-dimensional (2-D) gel electrophoresis and mass spectrometry coupled with Mascot searches. I identified 26 protein spots that displayed differential abundances in response to TSWV infection, which contained 37 proteins. Sixty two percent of these proteins were down-regulated by the viral infection demonstrating a complex response. Moreover, 8 and 11 protein spots that directly interacted with purified TSWV virions and a TSWV glycoprotein (GN), respectively, were identified in overlay assays of larval thrips proteins resolved by 2-D gel electrophoresis. A total of five proteins were identified from these spots. These interacting proteins might play roles in attachment and entry, endocytosis/exocytosis, and escape from different tissues for transmission to occur. Injection of double-stranded RNA (dsRNA) into adult female thrips triggered an RNAi response that resulted in 23% reduction of the target gene transcript level. This significant reduction resulted in increased mortality and decreased fertility compared to insects injected with control dsRNA or water and non-injected insects as well. The work presented here provides new insights on the molecular basis of this virus-vector interaction and describes new tools to conduct functional genomic assays to study gene function and design control strategies of F. occidentalis.
Keywords: Tospovirus; Thrips; Persistent propagative transmission; Proteomics; Two-dimensional gel electrophoresis; RNA interference